2004
DOI: 10.1097/00000542-200412000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Oral Gabapentin Reduces Elements of Central Sensitization in Human Experimental Hyperalgesia

Abstract: Oral gabapentin, administered to healthy volunteers in a regimen similar to that used in treating chronic neuropathic pain, reduces measures of central sensitization evoked by intradermal capsaicin. This suggests that the pain-relieving effect in chronic neuropathic pain condition is linked to the effect of gabapentin on central sensitization. The ability of the capsaicin model to detect the efficacy of this standard treatment of neuropathic pain suggests that it may have a predictive value for detection of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 0 publications
4
72
1
3
Order By: Relevance
“…daily dose of 2400 mg p.o. for 15 days, and this study revealed only effect on allodynia to brushing [73]. The study by Dirks et al, however, applied a rather low dose, and found an overall good effect on several pain parameters [68].…”
Section: Models Of Hyperalgesiacontrasting
confidence: 55%
See 1 more Smart Citation
“…daily dose of 2400 mg p.o. for 15 days, and this study revealed only effect on allodynia to brushing [73]. The study by Dirks et al, however, applied a rather low dose, and found an overall good effect on several pain parameters [68].…”
Section: Models Of Hyperalgesiacontrasting
confidence: 55%
“…It could be speculated that multiple dosing is necessary for drugs such as lamotrigine or tricyclic antidepressants, because these drug works in the clinic, but need time to develop the analgesia [73,[76][77][78].…”
Section: Figurementioning
confidence: 99%
“…Several groups have tested gabapentin against hyperalgesia and allodynia from cutaneous capsaicin stimulation. All studies showed analgesic effect on at least one hyperalgesia parameter (Dirks et al, 2002;Gottrup et al, 2004;Iannetti et al, 2005). One study showed no effect on subjective pain ratings, but only on brainstem activation in an fMRI study (Iannetti et al, 2005).…”
Section: Pharmacology Of Human Pain Modelsmentioning
confidence: 96%
“…In the hypertonic saline model, inducing muscle pain, an effect was seen in the study applying the lower dose. Segerdahl (2006) used a single dose of 1200 or 2600 mg distributed over 24 h, whereas Arendt- Nielsen et al (2007b) found effect of a single dose of 1200 mg. Gottrup et al (2004) applied a daily dose of 2400 mg p.o. for 15 days but revealed an effect only on allodynia in response to brushing.…”
Section: Models That Induce Endogenous Pain Modulationmentioning
confidence: 99%
“…52 A few human preclinical anticonvulsant studies may have relevance to postoperative pain given the nature of the experimental pain stimulus used. For example, gabapentin has been shown to reduce hyperalgesia following heat and topical capsaicin-induced sensitization 55 and also intradermal capsaicin injection 56 while hyperalgesia reduction with gabapentin after experimental first-degree burn failed to reach statistical significance. 57 In the case of lamotrigine, two studies failed to demonstrate any antihyperalgesic effect of this drug following heat and topical capsaicin-induced sensitization 58 or intradermal capsaicin injection.…”
Section: Preclinical Evidence Of Analgesic Efficacymentioning
confidence: 99%